1944
DOI: 10.1002/j.1551-8833.1944.tb20012.x
|View full text |Cite
|
Sign up to set email alerts
|

The Deterioration of Rubber Products by Micro‐Organisms

Abstract: ALTHOUGH rubber is generally regarded as being relatively inert, it is slowly attacked by certain microorganisms. This first came to the attention of the senior author when, due to a shortage of glass-stoppered bottles, an attempt was made to supplement them with rubber-stoppered bottles for studying the RO.D. of sea water. Almost invariably it was found that more oxygen was consumed by micro-organisms in sea water in the presence of rubber than in its absence. Even the small amount of rubber gasket exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1946
1946
2003
2003

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 10 publications
1
12
0
1
Order By: Relevance
“…In his studies on the disappearance of ethylene, H2C=CH2, from ripe apples and bananas, Nelson (96) overlooked the possibility of the microbial consumption of ethylene. The susceptibility to microbial attack of natural and synthetic rubbers, which are essentially polymers of unsaturated hydrocarbons, indicates that at least certain kinds of unsaturated hydrocarbons are easily oxidized by micro6rganisms (179). In recent experiments, we (178) have observed that cetene, C16Hrs, was oxidized from 13 to 30% faster by Desulfovibrio species than was cetane, C16H34.…”
Section: C113(chi)ech3mentioning
confidence: 97%
See 2 more Smart Citations
“…In his studies on the disappearance of ethylene, H2C=CH2, from ripe apples and bananas, Nelson (96) overlooked the possibility of the microbial consumption of ethylene. The susceptibility to microbial attack of natural and synthetic rubbers, which are essentially polymers of unsaturated hydrocarbons, indicates that at least certain kinds of unsaturated hydrocarbons are easily oxidized by micro6rganisms (179). In recent experiments, we (178) have observed that cetene, C16Hrs, was oxidized from 13 to 30% faster by Desulfovibrio species than was cetane, C16H34.…”
Section: C113(chi)ech3mentioning
confidence: 97%
“…Oxygen consumption in 60-ml glass-stoppered bottles of mineral solutions enriched with hydrocarbons as the only source of energy has been used for studying the occurrence and behavior of hydrocarbon oxidizers in marine materials (181). The same procedure has been used for studying the microbial assimilation of rubber hydrocarbons (179).…”
Section: Action Of Microtjrganisms On Hydrocarbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantity of oxygen consumed by the microbial attack of the rubber stoppers is negligibly small under ordinary experimental conditions as indicated by results in controls to which no oil was added (see second line of data in Table 6). In long-term or highly quantitative experiments, though, it must be recognized that most Binds of natural, compounded, and synthetic rubbers are slightly susceptible to microbial oxidation (ZOBELL and BECKWITH, 1944;BLAKE et al 1955). …”
Section: Amount Of Oil Oxidized By Bacteria In 100 Rnl Of Aerated Seamentioning
confidence: 99%
“…Oxygen consumption, in a glass-stoppered bottle filled to capacity with mineral solution enriched with hydrocarbon as the sole source of energy, has been used for studying the microbial oxidation of petroleum (77,234) and rubber (232) hydrocarbons. This B.O.D.…”
Section: Oxygen Uptakementioning
confidence: 99%